PERTANGGUNGJAWABAN PIDANA PELAKU PENGADANG LAJU AMBULANS PEMBAWA PASIEN EMERGENCY PERSPEKTIF PERATURAN PERUNDANG-UNDANGAN - Asep Suherman; Susi Ramadhani (UNIB Press, 2023)
ABSTRACT This article aims to identify and analyze in determining the perpetrator's mistakes and the application of criminal sanctions for the perpetrators of blocking the speed of ambulances carrying Emergency Patients. The type of research used is normative juridical, with a normative and conceptual approach. Primary legal material comes from Act Number 22 of 2009 concerning Road Traffic and Transportation. Secondary legal material in the form of publications about law other than official documents. The material collection is carried out by tracing sources on the internet and in printed form, the material is inventoried and grouped based on type classification and relevance. Described, analyzed deductively and/or inductively to draw conclusions and answer legal issues in research. Obstacles to the speed of ambulances carrying emergency patients often occur in various parts of Indonesia, even though these vehicles have priority rights that must take precedence over their speed on the road, as stipulated in the law on traffic and road transport. This act could have occurred from the attitudes and behavior of the perpetrators who were inhumane, indifferent, arrogant, insensitive, and irresponsible towards others. As a result, there are priority rights of road users that are neglected, harm the interests of patients, and even risk the patient dying before reaching the intended healthcare facility. A situation like this is of course very concerning to all parties. The imposition of social sanctions in the form of clarifications and apologies to the aggrieved parties does not guarantee a deterrent effect and may set a bad precedent in law enforcement going forward. The perpetrators must be sanctioned to be held accountable for their actions based on the applicable law, as a preventive and repressive effort in the future. Key words: Ambulance, Law, Responsibility. Criminal.